Evaluation of aggregate-cement paste Interface: Effects of aggregate characteristics on acid attack and permeability of concrete - Altwair, Nurdeen M.; Al-Kilani, Ashraf M.; Al-Tayeb, Mustafa M.; Putra Jaya, Ramadhansyah (Elsevier Ltd, 2026)
This investigation systematically evaluates the influence of aggregate type (basalt, white limestone, and brown limestone) and nominal size (10, 14, and 20 mm) on the characteristics of the interfacial transition zone (ITZ) and the durability of plain concrete, specifically its acid resistance and water permeability. The experimental program involved a comprehensive characterization approach. Aggregate surface roughness was quantified using a surface profilometer. The ITZ's microstructural and mechanical properties were analyzed via SEM, XRD, and direct tensile testing. Durability was assessed by evaluating acid resistance—determined by mass and compressive strength loss after 30-day immersion in 5 % H2SO4—and water permeability, measured in accordance with BS EN 12390–8:2019. The findings revealed that fractured aggregate surfaces significantly enhanced bond strength over sawn counterparts. A key mechanistic insight is that the nature of roughness, not just its magnitude, governs performance: naturally fractured aggregates are significantly rougher, with basalt's texture defined by high peaks (promoting mechanical interlocking) and limestone's by deep valleys. Basalt's chemical reactivity further improved the ITZ by consuming portlandite to create a denser, stronger interface, whereas limestone produced a more porous ITZ with unhydrated phases. Consequently, concrete incorporating basalt demonstrated superior acid resistance, with the least strength degradation and lowest permeability. White limestone performed moderately, while brown limestone showed the poorest resistance. Water penetration results aligned with these observations, confirming basalt concrete as the least permeable. For all aggregate types, using smaller sizes effectively mitigated acid damage and reduced permeability. The study underscores basalt's suitability for acidic environments due to its reactivity and ITZ refinement, stressing that aggregate selection and size are critical for designing durable concrete in corrosive conditions.